A biorefinery for efficient processing and utilization of spent pulp of Colombian Andes Berry (Rubus glaucus benth): Experimental, techno-economic and environmental assessment (2017)
This work investigated a model biorefinery for producing phenolic compounds extract, ethanol and xylitol from spent blackberry pulp (SBP). The biorefinery was investigated according to four potential scenarios including mass and heat integrations as well as cogeneration system for supplying part of the energy requirements in the biorefinery. The investigated SBP had 61.54% holocellulose; its total phenolic compounds was equivalent to 2,700 mg of gallic acid/100 g SBP, its anthocyanins content was 126.41 mg/kg of SBP and its total antioxidant activity was 174.8 μmol TE/g of SBP. The economic analysis revealed that the level of integration in the biorefinery significantly affected the total production cost. The sale-to-total-production-cost ratio indicated that both, mass and heat integrations are of importance relevance. The cost of supplies (enzymes and reagents) had the most significant impact on the total production cost and accounted between 46.72 and 58.95% of the total cost of the biorefinery.